Minuman Teh Celup Cascara dengan Penambahan Cengkeh (Syzygium aromaticum) - Hendrawan Saragih; Adi Ruswanto; Reza Widyasaputra (Program Studi Teknologi Hasil Pertanian, 2025)
This study is about cascara tea bag drinks with the addition of cloves (Syzygium aromaticum). This study aims to determine the effect of coffee skin drying time and the percentage of clove addition in making cascara tea bags, as well as to determine the ratio of drying time and percentage of clove addition that produces cascara tea bags preferred by panelists. This study used a Complete Block Design (CRD) with two factors. The first factor (Factor A) is the cascara drying time, which was tested at three different time levels, namely 4 hours (A1), 5 hours (A2), and 6 hours (A3). The second factor (Factor B) is the addition of clove powder with three different levels, namely 20% (B1), 30% (B2), and 40% (B3). The results of this study showed that variations in cascara drying time significantly affected water content, ash content, antioxidant activity, eugenol, taste preference test, color preference test, but did not significantly affect the total phenol analysis, and aroma preference test. However, varying drying time did not significantly affect the total phenol analysis and aroma preference test. Conversely, varying the amount of clove powder added significantly affected water content, total phenols, antioxidant activity, eugenol, and taste and color preferences, but did not significantly affect ash content or aroma preferences. Based on the overall organoleptic preference test, panelists scored between 4.57 and 5.14, with a rating of slightly liked.